2022
DOI: 10.4018/ijcac.312564
|View full text |Cite
|
Sign up to set email alerts
|

λHive

Abstract: Edge computing is a paradigm that brings computation and data storage closer to the location where it is needed to improve response times and save bandwidth. It applies virtualization technology that makes it easier to deploy and run a wider range of applications on the edge servers and take advantage of largely unused computational resources. This article describes the design and formalization of Hive, a distributed shared memory model that can be transparently integrated with JavaScript using a standard out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…However, it has been observed that the attitude towards receiving behavior also plays a significant role in actual behavior generation (Zhang et al, 2023;Guo et al, 2021). According to recent studies (Galván et al, 2022;Ilyas et al, 2022;Teragni & Pons 2022), farmers' behavior choices may not always align with their initial intentions due to subjective norms and other factors. This means that there may be a certain degree of deviation between farmers' intentions and their actual behavior, or that obstacles may arise during the process of translating intentions into actions.…”
Section: Willingness and Influencing Factorsmentioning
confidence: 99%
“…However, it has been observed that the attitude towards receiving behavior also plays a significant role in actual behavior generation (Zhang et al, 2023;Guo et al, 2021). According to recent studies (Galván et al, 2022;Ilyas et al, 2022;Teragni & Pons 2022), farmers' behavior choices may not always align with their initial intentions due to subjective norms and other factors. This means that there may be a certain degree of deviation between farmers' intentions and their actual behavior, or that obstacles may arise during the process of translating intentions into actions.…”
Section: Willingness and Influencing Factorsmentioning
confidence: 99%